2002
DOI: 10.1001/archotol.128.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Mucociliary Transport and Histologic Characteristics of the Mucosa of Deviated Nasal Septum

Abstract: Concave-side septal mucosae have impaired mucociliary transport, presumably due to ciliary loss, increased inflammation, and decreased density of the glandular acini.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
3
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 18 publications
1
51
3
7
Order By: Relevance
“…In many studies, it has been shown that NSD impaired the nasal MCC mechanism due to ciliary loss, increased inflammation and decreased density in glandular acini [4]. Polat et al [5] demonstrated that nasal mucociliary transport rates (NMTRs) of patients with a deviated septum were significantly lower than the NMTRs of the healthy controls on both the convex and concave sides.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, it has been shown that NSD impaired the nasal MCC mechanism due to ciliary loss, increased inflammation and decreased density in glandular acini [4]. Polat et al [5] demonstrated that nasal mucociliary transport rates (NMTRs) of patients with a deviated septum were significantly lower than the NMTRs of the healthy controls on both the convex and concave sides.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study by Jang et al [8] higher number of infiltrating inflammatory cells were seen in the concave side septal mucosa as compared to the convex side of septal mucosa and the difference was statistically significant. However, they obtained specimen 2 cm posterior to nostril and 1.5 cm inferior to nasal dorsum; in the present study specimen was taken from the most convex part of septum and its opposite side.…”
Section: Discussionmentioning
confidence: 60%
“…Other changes which are seen due to altered air flow dynamics are disturbed mucociliary dysfunction, lymphocytic infiltration and squamous metaplasia. Although these changes are seen on both sides of nasal mucosa, but are more severe on concave side [5][6][7][8][9]. All these changes can be avoided by surgically correcting DNS.…”
Section: Introductionmentioning
confidence: 99%
“…Septoplasti, nazal septum deviasyonun tek tedavisidir ve geçmiş yıllarda yapılan çalışmalarda belirtildiği gibi septoplasti sonrası mukosiliyer aktivitede artış saptanmaktadır (10). İntranazal tamponlar sıklıkla epistaksisi kontrol altına almak, septoplasti ve septorinoplasti sonrası kullanılır.…”
Section: Discussionunclassified